Everyday experiences of inclusion in Primary resourced provision: the voices of autistic pupils and their teachers. Issue 5 (20th October 2021) - Warren, Amber; Buckingham, Kate; Parsons, Sarah
ABSTRACT: Resourced provision is an important model for inclusive education, possibly providing the 'best of both worlds' for pupils with Special Educational Needs. Typically, pupils split their time between specialist and mainstream classes, offering balanced support that is highly valued by parents. However, there is little research about resourced provision from the perspectives of the pupils. This small-scale study explored how children and teachers experience resourced provision and manage the daily transitions between activities and classes. A qualitative visual storyboard methodology was co-created between the researchers and school staff and used to access the views of five pupils on the autism spectrum aged 9–11 years about their everyday experiences, including transitions between special and mainstream classes; six staff members from the resource base were also interviewed. Findings highlighted the importance of friendship and peers; where and how support was provided; tensions between structured and unstructured periods; and student/school identity. The school has implemented changes to how daily transitions are supported in response to pupils' views, with positive impacts on practice. The storyboard method is a simple and adaptable approach that can enable children to share their views in research and practice.